The role of neutrophil PD-L1 expression in acute exacerbation of COPD - Wei Sun; Liyu Zheng; Haibin Li; Li An; Jing Wang; Chao Ren (PLoS ONE, 2026)
Background and objective The elevation of neutrophil-lymphocyte ratio (NLR) has been shown to be critically involved in unfavorable outcomes among patients with chronic obstructive pulmonary disease (COPD). The mechanism underlying NLR changes during COPD progression remains unclear. This study evaluates the association between neutrophil PD-L1 expression and acute exacerbation of AECOPD and examines its correlation with the NLR. Methods In this prospective observational study from June 1 to December 30 2024, we enrolled 14 patients with acute exacerbation, 27 with stable conditions, and 9 healthy control subjects. Blood samples were collected for neutrophil isolation, and the CD15 + CD274 + neutrophil percentage was measured using flow cytometry. We also recorded and analyzed smoking history, pulmonary function test results, and blood routine test data. Results The percentage of CD15 + CD274 + neutrophils was notably higher in patients with COPD compared to healthy controls and was even more elevated in those experiencing acute exacerbations of COPD (AECOPD) than in patients with stable COPD. This increased percentage was positively correlated with NLR but negatively correlated with FEV 1 % (FEV 1 percentage of the predicted value). The AUC of CD15 + CD274 + neutrophil percentage for predicting AECOPD was 0.894 with 95% CI 0.8–0.989 and a ratio above 3.273 (odds ratio 1.386; 95% CI 1.016–1.891; P = 0.039) independently associated with AECOPD. Conclusion Peripheral blood neutrophil PD-L1 expression was elevated in AECOPD and independently associated with exacerbation status in this pilot cohort. Larger, multi-center studies with mechanistic validation are required to determine its clinical utility.